Potencial de biossorventes de baixo custo na remoção dos corantes violeta cristal e fucsina básica em sistema contínuo e descontínuo de adsorção - Salomón, Yamil Lucas de Oliveira (2020)
The potential of pecan pericarp (Carya illinoensis), Pacara Earpod tree seed residues (Enterolobium contortisilquum), and ironwood seed residues (Caesalpinia leiostachya) were evaluated for the removal of crystal violet (CV) and basic fuchsin (BF) dyes through continuous and batch adsorption system. The biosorbents were called pecan pericarp powder (PPP), pacara ear pod seed residues (PETS) and ironwood seed waste (IWS). The PPP biosorbent was used to remove the CV dye and the PETS and IWS biosorbents were tested to remove BF. The morphological characteristics of the materials present rough surfaces and different sizes. Also, the biosorbents showed functional groups associated with cellulose, lignin, and hemicellulose. The ideal dosage was 0.05 g / 100 mL in PPP and 1 g L-¹ for PETS and IWS. The best pH was set at 8.5 for CV biosorption in PPP, and pH 9.0 for PETS and IWS biosorption in BF. The kinetic profile was better adjusted for the general order model, and the balance was reached quickly in the first 5 min for the different initial concentrations of the CV. In PETS and IWS kinetics, the pseudo-second order model was considered more appropriate to describe BF biosorption. The PPP balance curves in CV were best described by the Langmuir model, with a maximum biosorption capacity of 642 mg g-¹, reaching 328 K. The Langmuir and Tóth models were the best to represent the balance curves for BF in PETS and IWS, respectively. The isotherm experiments showed maximum capacities of 166.858 mg g-¹ (PETS) and 110.317 mg g-¹ (IWS), with an initial concentration of 500 mg L-¹ at 328 K. The thermodynamics was favorable and endothermic for PPP and for the biosorbents PETS and IWS the process was spontaneous, endothermic and favorable. In the simulated effluent experiment, color removals were 94.1% with PPP, 66% with PETS, and 54% with IWS. Finally, the materials were tested in a fixed bed. For the PPP biosorbent, the column operated for 52.5 hours at a height of 25 cm, and the models suitable for describing the dynamic curves were the models of Thomas, Bohart-Adams, and Yoon-Nelson. The PETS and IWS biosorbents were also used in a fixed bed, reaching break times of 710 and 415 minutes, with a biosorption capacity of 124.5 mg g-¹ and 76.5 mg g-¹, respectively. Therefore, materials plant residues can be used as effective biosorbents for the treatment of aqueous effluents containing the dyes CV and BF in a continuous and batch system.